Isolation and characterization of Ligustrum micranthum (Oleaceae) microsatellite loci using paired‐end Illumina reads. Issue 1 (14th January 2016) - Sugai, Kyoko; Setsuko, Suzuki
Abstract: Twenty‐six microsatellite loci were developed and characterized for L igustrum micranthum, a species endemic to the Ogasawara Islands, Japan. The genetic structure of this species must be clarified in order to restore the island's ecosystem. A total of 8511 primer pairs were designed from de novo sequencing. Of the 48 primer pairs selected, amplification and polymorphisms were tested using one population each from the Chichijima and Hahajima Islands of the Ogasawara Islands. Twenty‐six microsatellite loci were successfully amplified and the number of alleles for these loci ranged from five to 31 per locus, and the mean expected heterozygosities were 0.858 and 0.849, respectively. No significant deviation from the Hardy–Weinberg equilibrium was observed in either population, and no significant linkage disequilibrium was detected between any locus pair. The microsatellite loci reported in this study can be used in future studies to evaluate the genetic structure and mating system of L . micranthum . Abstract : Twenty‐six microsatellite loci were developed and characterized for Ligustrum micranthum Zucc. (Oleaceae), a species endemic to the Ogasawara Islands, Japan. These microsatellite loci can be used in future studies to evaluate the genetic structure and mating system of L. micranthum .